Defense Responses to Short-term Hypoxia and Seawater Acidification in the Thick Shell Mussel Mytilus coruscus - Sui, Yanming; Liu, Yimeng; Zhao, Xin; Dupont, Sam; Hu, Menghong; Wu, Fangli; Huang, Xizhi; Li, Jiale; Lu, Weiqun; Wang, Youji (Frontiers in Physiology, 2017)
The rising anthropogenic atmospheric CO2 results in the reduction of seawater pH, namely ocean acidification (OA). In East China Sea, the largest coastal hypoxic zone was observed in the world. This region is also strongly impacted by ocean acidification as receiving much nutrient from Changjiang and Qiantangjiang, and organisms can experience great short-term natural variability of DO and pH in this area. In order to evaluate the defense responses of marine mussels under this scenario, the thick shell mussel Mytilus coruscus were exposed to three pH/pCO2 levels (7.3/2800µatm, 7.7/1020µatm, 8.1/376µatm) at two dissolved oxygen concentrations (DO, 2.0, 6.0 mg L-1) for 72 h. Results showed that byssus thread parameters, such as the number, diameter, attachment strength and plaque area were reduced by low DO, and shell-closing strength was significantly weaker under both hypoxia and low pH conditions. Expression patterns of genes related to mussel byssus protein (MBP) were affected by hypoxia. Generally, hypoxia reduced MBP1 and MBP7 expressions, but increased MBP13 expression. In conclusion, both hypoxia and low pH induced negative effects on mussel defense responses, with hypoxia being the main driver of change. In addition, significant interactive effects between pH and DO were observed on shell-closing strength. Therefore, the adverse effects induced by hypoxia on the defense of mussels may be aggravated by low pH in the natural environments.